If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5n + -9 = -54 Reorder the terms: -9 + -5n = -54 Solving -9 + -5n = -54 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -5n = -54 + 9 Combine like terms: -9 + 9 = 0 0 + -5n = -54 + 9 -5n = -54 + 9 Combine like terms: -54 + 9 = -45 -5n = -45 Divide each side by '-5'. n = 9 Simplifying n = 9
| 3*-5+4*y=12 | | x+6y^2=8 | | 3*-10+4*y=12 | | x+17+3x+1=90 | | (4x+17)=(5x-1) | | x^2-86x+1320=0 | | 3X^3=15 | | (3)(12)+8x=86 | | 16+8y=12y | | 3*-14+4*y=12 | | 4(5x+3)=28 | | x-45+150=180 | | -4x-1/3=35/3 | | x+4+132=180 | | (3y+8)=(6y-1) | | 4x-1/3=35/3 | | 6x+(2)(15)=150 | | -5y+6=-7y-14 | | (6x)=(5x+9) | | 8y-3=5(y+6) | | 3x-20=6x-8 | | 10+3y=-6 | | S=Ngj | | 3(2+x)=-36 | | x^2-2400=0 | | -2g-6=-9 | | 360=(6+3w)(w) | | 18+0.5x=25 | | 3(2c-5)+2c= | | -8w-2=-10-4w | | 4x+6-x=22+6 | | -1/3(9s-36t=-5)= |